Problems and Solution of Malabsorption Syndrome in Indonesia - Suharjono, Suharjono; Sunoto, Sunoto; Budiarso, Aswitha; Pusponegoro, Titut S.; Tumbelaka, W.A.F.J. (Paediatrica Indonesiana, 2017)
I. Problems of malabsorption syndrome in developing countries like lndonesia are associated especially with : (1) Protein Calorie Malnutrition (2) Low Birth Weight (3) Gastroenteritis (4) Post bowel surgery (5) Being unused to drink milk after weaning. They show a big difference with those in developed countries where they usually are correlated with a.o. coeliac disease, cystic fibrosis, etc. II. Solving the problems : a. Since in diarrhoeal patients, with or without PCM, sugar intolerance and or fat malabsorption usually occur, a formula consisting of low or free lactose with easily absorbable fats i.e. MCT or UFA, might be the best solution as a refeeding regimen. b. Besides treating the malabsorption syndrome, other measures are much more important i.e correction of fluid and electrolyte imbalance and treatment of predisposing condition.